Push-Up Counter (PUC) as an instrument of arm muscle strength: Validity and reliability - Artanayasa, I Wayan; Kusuma, Ketut Chandra Adinata; Ariawan, Ketut Udy (Journal Sport Area, 2023)
Accurate physical condition measurement results are obviously determined by the quality of the instrument, namely a valid and reliable instrument. Developing a push-up measurement tool combined with technology is an urgent need. Moreover, this study aims to determine the validity and reliability of the Push-Up Counter (PUC) as a sensor-based measurement of arm muscle strength. This research is development research that focuses on uncovering the validity and reliability values of PUC using a quantitative approach. The validity value was obtained from the assessment of three experts by conducting questionnaire which has four main aspects, namely: instructions, components, safety, and usage. 30 athletes/students were involved as the subject participants in measuring the PUC reliability. Furthermore, the data collection were analyzed by using SPSS to determine the value of r. This study found that the PUC was valid (r = 0.88). The Cronbach Alpha value of this reliability instrument was r = 0.41. Referring to the validity and reliability result, it can be concluded the PUC was feasible and elligible to be used in measuring the arm muscle strength in the process of physical test. However, PUC operation is not yet integrated with smartphones. These results also provide opportunities for further research in developing application-based PUC devices or Android.